Stability of Aerobic Granular Sludge for the Treatment of Inorganic Wastewater in a Sequencing Batch Reactor - LI Zhenghao; LUO Yi; LIU Liliang; KANG Jianlin; LI Guangming; NIE Jiale; LONG Bei (Renmin Zhujiang)
Four sequencing batch reactors (SBR, R1, R2, R3 and R4) were started by seeding aerobic granular sludge (AGS), AGS/stereohollow packing media, AGS/polyurethane sponge packing media, and AGS/stereohollow packing media/polyurethane sponge packing media, respectively, so as to explore their nitrogen removal performances and granular stability in treating inorganic wastewater with high ammonia nitrogen (250~500 mg/L). In Days 1~30, the breakage of a large number of granules and the significant decrease of sludge concentration were observed in the four reactors. After the addition of AGS on Day 31, AGS with small particle size gradually dominated and maintained its stability in R1, and the coexistence of biofilm and AGS gradually realized in R3. However, the continuous granular disintegration process was repeated again in R3 and R4. R1 demonstrated the removal efficiencies of approximately 48% and 99% for total inorganic nitrogen (TIN) and ammonia nitrogen, respectively. The attached growth of biofilm on stereohollow packing media in R2 was successfully achieved within 30 days. However, its nitrogen removal performance fluctuated greatly, and the reactor eventually demonstrated the removal efficiencies of approximately 49% and 99% for TIN and ammonia nitrogen, respectively. The attached growth of biofilm on polyurethane sponge packing media in R3 was successfully realized within 7 days. The reactor showed good impact load resistance, and the removal efficiencies of TIN and ammonia nitrogen were approximately 52% and 99%, respectively. In R4, the attached growth of biofilm on stereohollow packing media was completed within 40 days, while the attached growth of biofilm on polyurethane sponge packing media was successfully achieved within 10 days. Its nitrogen removal performance was unstable, and the removal efficiencies of TIN and ammonia nitrogen were approximately 40% and 99%, respectively.